Innovative Method for Biomethane Production Based on a Closed Cycle of Biogas Upgrading and Organic Substrate Pretreatment—Technical, Economic, and Technological Fundamentals - Joanna Kazimierowicz; Marcin Dębowski; Marcin Zieliński (Energies)
This study presents the technological, technical, and economic basis of the solution developed by the authors for the production of biomethane based on the pretreatment of organic substrates at low temperature using solidified CO2 captured during biogas upgrading in a closed cycle (TeCH4BiogasUp). TeCH4BiogasUp integrates the disintegration of organic substrates, biogas upgrading and the sequestration and utilization of CO2 in a closed cycle. The multifunctional and hybrid nature of TeCH4BiogasUp sets it apart from other available solutions that only perform selected, individual technological processes. This is a significant advantage and a competitive market edge; however, it also poses challenges in conducting comparative analyses with existing solutions on the market. The technology has been compared with traditional substrate pretreatment techniques and biogas purification technologies. Considering the origin of the solidified CO2, this method can be regarded as material recycling, which aligns fully with the principles of the circular economy. This technology supports the reduction in CO2 emissions by capturing the CO2 and introducing it into the closed process. This novel approach to the production and utilization of solidified CO2 largely overcomes previous limitations associated with the low profitability of the process. TeCH4BiogasUp could serve as a viable alternative to other methods, particularly in light of economic trends and the imperative to reduce CO2 emissions through the development of renewable energy sources.